SOLVE THE FOLLOWING EQUATIONS :

1.a(a2+b2)x2 + b2x - a = 0

2.9x2 - 9(a+b)x + (2a2+5ab+2b2) = 0

1.        a = a(a2 + b2)         b = b2      c = -a

            b2 - 4ac = (b2)2 - 4 [ a(a2 + b2) ] ( -a )

                          = b+ 4a [ a3 + ab2 ] 

                          = b4 + 4a4 + 4a2b2

                          = (2a2+b2)2

                     X =  -b +   root b2 - 4ac / 2a                     or                -b -   root b2 - 4ac / 2a

                        =  -b2 + 2a2 + b /  2 * a(a2 + b2)         or                -b2 - 2a2 - b2 /  2 * a(a2 + b2)  

                        =  2a2 / 2a(a2 + b2)                              or                 -2(b2 + a2)   / 2a(a2+b2)  

                        =  a / (a2 + b2)                                      or                 -1 / a

  • 24

 a=9     b=-9a-9b       c=(2a2+5ab+2b2)

b2- 4ac = (-9a-9b)2- 4 (9) (2a2+5ab+2b2)

              = 81a2 + 81b2 + 162ab - 72a2 - 72b2 - 180ab

              = 9a2 + 9b2 -18ab

              = 9(a-b)2

X =  9a + 9b + 3a -3b / 18             (or)            9a + 9b - 3a + 3b / 18

   =  12a + 6b / 18                         (or)            12b + 6a / 18

   =  2a + b  /  3                             (or)             2b + a  /  3 

  • 7

thanks a lot !!!!

for you thumbs up !!!!!

ALL THE BEST !!!!!!

  • -2

It was really helpful:)

thnx 4 asking the doubt

  • -1

. Solve for x : (a-b)^2 + 2(a^2 - b^2)x + (a + b)^2 = 0

  • -1
What are you looking for?